Identification and evaluation of 4-anilinoquin(az)olines as potent inhibitors of both dengue virus (DENV) and Venezuelan equine encephalitis virus (VEEV). (15th November 2021) - Saul, Sirle; Huang, Pei-Tzu; Einav, Shirit; Asquith, Christopher R.M.
Graphical abstract: Abstract: There is an urgent need for novel strategies for the treatment of emerging arthropod-borne viral infections, including those caused by dengue virus (DENV) and Venezuelan equine encephalitis virus (VEEV). We prepared and screened focused libraries of 4-anilinoquinolines and 4-anilinoquinazolines for antiviral activity and identified three potent compounds. N -(2, 5-dimethoxyphenyl)-6-(trifluoromethyl)quinolin-4-amine (10 ) inhibited DENV infection with an EC50 = 0.25 µM, N -(3, 4-dichlorophenyl)-6-(trifluoromethyl)quinolin-4-amine (27 ) inhibited VEEV with an EC50 = 0.50 µM, while N -(3-ethynyl-4-fluorophenyl)-6, 7-dimethoxyquinazolin-4-amine (54 ) inhibited VEEV with an EC50 = 0.60 µM. These series of compounds demonstrated nearly no toxicity with CC50 values greater than 10 µM in all cases. These promising results provide a future prospective to develop a clinical compound against these emerging viral threats.